Kedudukan Kepala Daerah Sebagai Pejabat Pembina Kepegawaian Dalam Pemilihan Umum Kepala Daerah - Stendo Berthyno Sitania; Hendrik Salmon; Andress Deny Bakarbessy (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: In Head of Local Governments’ positionasthe Chief ofEmployee Management who own authority to appoint, mutate, anddischargeCivil Servant Employees thenhe/she could intimidate the CSEs to involveinGeneral Election process.Purposes of the Research: To study and analyze the position of the regional head as a staffing officer in the general election of the regional head.Methods of the Research: Type of research: normative juridical, the approach used is the statute approach, the conceptual approach, and the case approach. The sources of legal materials used are Primary Legal Materials, Secondary Legal Materials and Tertiary Legal Materials.Results of the Research: The result of this research shows that political patronage stillhappened because position of the Head of Local Government aspolitical officer includesas the Chief ofEmployee Management where position still themostly found factorin the fieldwhenabuse of neutralitycommitedbyCivil Servant EmployeesinGeneral Election.